Pendampingan Penyusunan Kajian Lingkungan Hidup Strategis sebagai Dasar dalam Pembangunan Berkelanjutan di Provinsi Kalimantan Tengah: The Assistance of the Preparation of Strategic Environmental Assesment as A Foundation for Sustainable Development in the Province of Central Kalimantan - Yulianti, Nina; Adji, Fengky Florante; Hukom, Alexandra; Nomeritae, Nomeritae; Segah, Hendrik; Munier, Muhammad Taswin; Tembalang, Paulus; Putra S, Ravenalla Abdurrahman Al Hakim Sampurna (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The sustainable development goals (SDGs) are agreed-upon common goals that must be met by all nations by 2030. Efforts to meet the SDG targets are a national development priority that necessitates the coordination of planning policies at the national and regional levels. In Central Kalimantan, the provincial and district/city governments are currently preparing various Strategic Environmental Assessment documents (SEA). The goal of this activity is to increase the working group's and experts' understanding of the principles of sustainable development that have become the basis and integrated into the development of a region, so that they can provide recommendations for environmental considerations at the strategic decision-making level, particularly after the 2024 joint national and provincial election. It has been carried out to reduce the obstacles that have previously been a problem by providing technical guidance on various tools for preparing and validating SEA. Following the training, it was discovered that the understanding and mastery of district/city working groups and university experts could improve compared to before the assistance series.